Kamini, a little recognised source of illicit opioid: A case series of 12 patients. (12th May 2022) - Khan, Tabibul; Ariyawansa, Pem; Quinn, Janette; Hayllar, Jeremy
Abstract: Introduction: This case series describes 12 patients who developed opioid use disorder after ingesting a prohibited, imported herbal product, Kamini, which contains Papaver somniferum . They appeared unaware of the risk of dependence from Kamini and most had struggled to manage their use for many months before presenting for treatment. Methods: After two cases were presented at a clinical meeting, a chart review was conducted of cases across four public opioid treatment clinics in south‐east Queensland with about 1500 patients registered, identifying 10 further cases. Results: Twelve patients presented with features of opioid withdrawal, seeking treatment after use of Kamini for periods between 6 months and 8 years. Eleven patients were born in India. Nine patients stabilised on buprenorphine maintenance treatment, three of whom commenced long‐acting injectable buprenorphine. One patient left after 1 day and subsequently began methadone treatment with a private prescriber. Two patients on smaller doses and shorter‐term use undertook withdrawal with prescribed (off‐label) trans‐dermal buprenorphine. One patient, initially lost to follow‐up, later stabilised on long‐acting injectable buprenorphine. Reasons for presenting included supply shortages and financial distress during the COVID‐19 pandemic. Discussion and Conclusion: Kamini represents an illicit source of non‐prescription opioid in Australia. Although classified as an illegal import by the Therapeutic Goods Administration, patients confirm that it is readily available in Brisbane. Targeted efforts are needed to prevent further patients developing opioid dependence from use of Kamini and also to highlight treatment options for those seeking to stop Kamini use.